NANOCELLULOSE CONTAINING HIGH CONSISTENCY FURNISHES; SMALL SCALE TESTING - Dimić, Katarina; Maloney, Thaddeus; Paltakari, Jouni; Sanavane, Yogesh (Journal of Applied Engineering Science, 2013)
Nanotechnology allows development of new enabling technologies with broad commercial potential. Cellulose has also the potential to be the source for renewable materials, which can be made multifunctional and self-assembling  at the same time displace many non-renewable materials including metal and ceramics. The potential application area includes high quality paper products, paper coatings, high-performance and sustainable composites.Research has focused on small scale testing odnanocellulosesuspensions and matrix of furnish materials in order to study new composite materials. Basic rheological and dewatering properties of nanocellulose based high consistency furnishes were evaluated. Two different grades of nanocellulose, microfibrillated cellulose (MFC) and nanofibrillated cellulose (NFC) with different swelling properties were used. Both types of nanocellulose have a common challenge, namely strong interactions between the particles resulting in aggregation of individual particles. These inter-particle interactions together with the physical entanglements cause high viscosities of nanocellulose suspensions and furnishes, which together with high water bonding property affects processability
Keywords: NFC; MFC; Rheologyology; Nanocellulose